2020
DOI: 10.3390/su12020684
|View full text |Cite
|
Sign up to set email alerts
|

Fire Evacuation in Metro Stations: Modeling Research on the Effects of Two Key Parameters

Abstract: Metro lines have undergone a rapid development in China and a large number of metro stations have also been built. The passenger traffic volume has reached or exceeded the designed transport capacity in some big cities such as Beijing and Shanghai. The safety evacuation problem within metro stations under emergency has become a worldwide concern. In this study, BuildingEXODUS was employed as the simulation platform and a metro station in Shanghai was selected for model development. Based on field survey data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Mass audience venues with high-density pedestrian flows, rapid oxygen consumption, limited space for movement, and fixed exits are always the research focus in safety evacuation, including railway stations [170], subway stations [15,171], airports [31], hospitals [99,102], schools [108,120], commercial buildings [65], residential buildings [107,128], and public places of entertainment [172][173][174]. Safety evacuation of offshore platforms are one of the frontiers of research and a new branch in offshore engineering to which increasing attention has been paid [122].…”
Section: Evacuation Environmentsmentioning
confidence: 99%
“…Mass audience venues with high-density pedestrian flows, rapid oxygen consumption, limited space for movement, and fixed exits are always the research focus in safety evacuation, including railway stations [170], subway stations [15,171], airports [31], hospitals [99,102], schools [108,120], commercial buildings [65], residential buildings [107,128], and public places of entertainment [172][173][174]. Safety evacuation of offshore platforms are one of the frontiers of research and a new branch in offshore engineering to which increasing attention has been paid [122].…”
Section: Evacuation Environmentsmentioning
confidence: 99%
“…This work focuses on evacuating occupants in different positions to determine optimal evacuation exit. The OPS is used to measure the utilization rate of evacuation passageway and exit [24], and can be expressed as follows:…”
Section: Problem Statementmentioning
confidence: 99%
“…Research found that typical evacuation strategies have been adopted by metro passengers in accidents, for example, ripple evacuation, shortest-path evacuation, herd evacuation, and so on [18]. Furthermore, factors affecting evacuation have also received attention, such as automatic ticket checkers, stair width, walking speed, and so on [19,20]. Secondly, the emergency response process is a research hotspot for metro emergency management, mainly focusing on the detection of underlying conflicts in metro emergency response process with respect to time, order, and resources [6].…”
Section: Metro Emergency Managementmentioning
confidence: 99%